INOVASI TEKNOLOGI PELOROT MALAM, KONTEN KREATIF, DAN PENCAMPURAN PEWARNAAN ALAM DAN SINTETIS UNTUK PENINGKATAN KUALITAS DAN KAPASITAS BATIK TULIS DI BANGKALAN - Tampubolon, Liosten Rianna Roosida Ully; Zuraidah, Safrin; Borman, Muhammad Syahrul; Siswadi, Siswadi (Jurnal Likhitaprajna, 2024)
The production process of Batik Tulis in Paseseh Village, Tanjung Bumi Subdistrict, Bangkalan Regency uses conventional methods starting from batik with canting, the fixation process of mixing colouring and ngelorot malam so that there are problems, namely: production capacity, product quality and competitiveness are still low. The purpose of the empowerment programme for business partners of regional superior products is to provide the application of technological innovations in the malam pelorot machine, mixing natural and synthetic dyes and creative content so as to increase production capacity, minimise product damage, sales volume, batik craftsmen's profits and product competitiveness. The method used is in the form of training, mentoring and practice of technological innovation to partner 1 and partner 2: 1) Night pelorot machine in partner 2: can increase production capacity by 40%, defective product damage rate decreased by 3%, company profits increased by 35%, and sales volume increased by 30%, 2) Training, mentoring and practice of mixing natural and synthetic colouring can increase the knowledge of partner 1 and partner 2 by 30% to 65%, 3) Training, Mentoring and Practice of Creative Content Creation can increase knowledge and skills in creative content creation for partner 1 and partner 2 by 60%.